Boosting English Reading Proficiency: The Efficacy of the KWL Learning Strategy - Miranti Eka Putri (Universitas Hamzanwadi, 2023)
In the contemporary globalized society, addressing the challenges of low academic performance and limited English reading comprehension is paramount. This study investigates the potential of the KWL (Know-Want-Learned) learning strategy, a technique posited to enhance student outcomes, in bridging the observed gap between theoretical pedagogies and practical interventions. Utilizing a quasi-experimental design, diverse students from varied grades and backgrounds were divided into two groups: one exposed to the KWL technique and another receiving traditional instruction. Standardized tests were employed to measure outcomes. Notably, students undergoing KWL-based instruction exhibited significant advancements in academic performance and English reading comprehension. These findings underscore the value of integrating the KWL strategy into educational curricula. While the results are promising, further studies are warranted to understand the long-term effects and the strategy's adaptability across diverse educational settings and demographics. In essence, this research not only highlights the pressing educational challenges but also introduces an evidence-backed solution for substantial improvement.